1997
DOI: 10.1021/la961045+
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Particle Size on pH, Electrolyte, and Time for Expandable Copolymer Latexes by Hydrodynamic Fingerprinting

Abstract: A new technique, hydrodynamic fingerprinting, is presented for the characterization and study of expandable latex dispersions on the basis of their hydrodynamic behavior. In the hydrodynamic fingerprint the hydrodynamic size as measured by photon correlation spectroscopy is presented as a function of two colloidal state variables simultaneously, pH and pλ, where pλ is the logarithm of the conductivity. Hydrodynamic fingerprinting is applied to two methyl methacrylate-ethyl acrylate latexes, one of which contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The term brush denotes that the grafting density r (number of grafted chains per unit area) is high enough so that the chains are enforced to take a stretched conformation [1]. These systems have received a great deal of attention in recent years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Polyelectrolyte brushes are interesting from the point of view of fundamental as well as of applied research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term brush denotes that the grafting density r (number of grafted chains per unit area) is high enough so that the chains are enforced to take a stretched conformation [1]. These systems have received a great deal of attention in recent years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Polyelectrolyte brushes are interesting from the point of view of fundamental as well as of applied research.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the complex experimental behavior of these spherical polyelectrolyte brushes is usually showed as a fingerprint for each system in particular [15]. This fingerprint is a 3D plot of the hydrodynamic size vs. solution pH and pk (k is the electrical conductivity of the medium).…”
Section: Introductionmentioning
confidence: 99%
“…The hydrodynamic size values for a certain sample, obtained by dynamic light scattering, are larger than those obtained from transmission electron microscopy technique; the hydrodynamic size can change with the suspension condition . In the case of our samples, the size determined by DLS for the CoxNP1 has been found to be 129 nm, whereas the size of the PoxNP1 nanoparticles was larger, that is, 290 nm.…”
Section: Resultsmentioning
confidence: 55%
“…Fingerprinting (6)(7)(8), a means of representing colloidal variables as a function of pH and the log of the conductivity, pλ, was conceived at the University of Massachusetts in 1986. The conductivity is expressed in units of microsiemens per centimeter, which is convenient as it places the zero close to the conductivity of pure distilled water.…”
Section: Introductionmentioning
confidence: 99%
“…The conductivity is expressed in units of microsiemens per centimeter, which is convenient as it places the zero close to the conductivity of pure distilled water. Rowell and co-workers (6)(7)(8) have suggested that the solution conductivity is the experimental analogue to the ionic strength. It has the advantage of being a measured quantity that does not depend on a knowledge of the ions present in solution.…”
Section: Introductionmentioning
confidence: 99%